Losy nauczycieli Wielkopolski wschodniej w czasie II wojny światowej w świetle zapisów kronik szkolnych. Wprowadzenie do problematyki - Gołdyn, Piotr (Biuletyn Historii Wychowania, 2017)
School chronicles are an important but sometimes underestimated source of information for the history of education. The difficulties with their use result from their dispersion, lack of availability and subjective nature. However, despite their subjectivity, they can provide extremely interesting information, e.g. on the biographies of individual educators. This article focuses on the war fate of school teachers in the Eastern Greater Poland. Almost all of them lost their jobs as a result of the closure of schools. Many were deported to the General Government or to forced labour in Germany. Those who stayed undertook off-an-on work or jobs that had nothing to do with the teaching profession. Despite the threat to their lives, some of them were also engaged in secret teaching. Unfortunately, there were also those who decided to collaborate with the German occupier. The research included in this article should be considered an introduction to research in this source area.